Reposition of Ihdad Women’s Multi-Career Perspective: Philosophical, Historical, Juridical, and Sociological Studies - Akbar, Wahyu; Tarantang, Jefry; Mujiburohman, Mujiburohman; Ridwan, Ahmad Hasan; Sururie, Ramdani Wahyu (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Repositioning the ihdad of career women is a phenomenon that involves changing the role and position of women in a professional context. A multi-perspective approach is needed for a complete grasp of this phenomenon, including philosophical, historical, juridical, and sociological studies. The research method is the normative method with a literature review (library research) with a phenomenological approach, historical approach, philosophical or philosophical approach to Islamic law (ushul fiqh), juridical approach (regulations and fatwas), and sociological approach, then combined with retrospective methods and analyzed qualitatively. According to the results, a thorough comprehension of women’s shifting roles and positions in the workplace can be seen in the repositioning of ihdad from a philosophical, historical, legal, and sociological standpoint. From a philosophical perspective, career women’s ihdad repositioning involves considerations of gender equality, justice, and human dignity. From a historical perspective, career women’s ihdad repositioning reflects significant social changes in the role and position of women in the workplace. Historically, women were often restricted to domestic roles and deemed unsuitable for careers outside the home. From a juridical perspective, career women’s ihdad repositioning involves a legal analysis related to the protection and rights of women in the workplace. From a sociological perspective, career women’s ihdad repositioning involves an analysis of social structures and social interactions that affect women’s position in the world of work.